In Situ Bioremediation in Mixed-culture Inoculated Biological Permeable Reactive Barrier Systems - Evans M.N. Chirwa; Karisa Naidu; Buyisile Kholisa; Mpumelello T. Matsena; Boitumelo F. Mashangoane; Pulane E. Molokwane (Chemical Engineering Transactions, 2023)
Cr(VI) reducing bacteria was isolated from dried sludge collected from sand drying beds at a local wastewater treatment plant in Brits (South Africa). The plant received high periodic loadings of Cr(VI) contaminated effluent from an abandoned chrome processing foundry within the chrome mining town of Brits. The isolated bacteria were tolerant to high Cr(VI) loadings with significant chromium removal activity at loadings up to 80 mg(L-1 under continuous flow conditions. The active species in the sludge culture were determined to be predominated by Bacillus thirungiensis, Bacillus cereus, Lycinobacillus sphaerococcus. The isolated consortium culture was introduced as a biocatalyst in a microbial permeable bioreactive barrier for treatment of Cr(VI) contaminated water through soil medium. When tested in continuous flow bench-scale systems, the steady-state condition was attained after the reactor's operation for 25 days. Time course concentration profiles in batch tests fitted well with first- and second-order exponential rate equations yielding first-order rate constants in the range of 0.615 h-1 and 0.0532 L(mg-1(h-1 for Cr(VI) loadings ranging from 50 to 400 mg/L. The laboratory scale studies showed that the biological permeable reactive barrier technology using indigenous microbes has potential application for hexavalent chromium remediation in contaminated environments. Finally, the technology using bacteria in-situ shows that Cr(VI) can be remediated in the environment using a passive system at a low cost with minimum intervention.